Dynamic federalism for Sarawak: issues and challenges - Abang Bolhil, Abang Ikhbal; Mokhtar, Khairil Azmin (2019)
The Federation of Malaysia came into being on 16 September 1963 with the merger of the States of Malaya, Singapore, Sarawak and North Borneo. In the asymmetry federation Sarawak was guaranteed with more autonomy compared to the States of Malaya as agreed in the Malaysia Agreement 1963. The additional power can be observed in Part VI of the Malaysian Constitution which need to be read together with the Ninth Schedule of the Constitution that established the constitutional framework of the relationship between the Federal government and the State governments. Since the formation of Malaysia Sarawak have experienced various violations of its right by the federal authority in spite of the existence of constitutional safeguards for the states. This is a qualitative research and legal study which include field study such as interviews. This study seeks to identify issues and challenges in protecting Sarawak’s rights within Malaysia federal system. It is believed that protection of rights of Sarawak as one of the states that have special position in the Malaysian Constitution can be more effective by applying the concept of dynamic federalism.